Dependence of the amplitude of magnetosonic waves on the solar wind and AE index using Van Allen Probes. Issue 6 (5th June 2017) - Kim, Kyung‐Chan; Shprits, Yuri
Abstract: We present the dependence of the magnetosonic wave amplitudes both outside and inside the plasmapause on the solar wind and AE index using Van Allen Probe‐A spacecraft during the time period of 1 October 2012 to 31 December 2015, based on a correlation and regression analysis. Solar wind parameters considered are the southward interplanetary magnetic field (IMF B S ), solar wind number density ( N SW ), and bulk speed ( V SW ). We find that the wave amplitudes outside (inside) the plasmapause are well correlated with the preceding AE, IMF B S, and N SW with time delays, each corresponding to 2–3 h (3–4 h), 4–5 h (3–4 h), and 2–3 h (8–9 h), while the correlation with V SW is ambiguous both inside and outside the plasmapause. As measured by the correlation coefficient, the IMF B S is the most influential solar wind parameter that affects the dayside wave amplitudes both outside and inside the plasmapause, while N SW contributes to enhancing the duskside waves outside the plasmapause. The AE effect on wave amplitudes is comparable to that of IMF B S . More interestingly, regression with time histories of the solar wind parameters and the AE index preceding the wave measurements outside the plasmapause shows significant dependence on the IMF B S, N SW, and AE : the region of peak coefficients is changed with time delay for IMF B S and AE, while isolated peaks around duskside remain gradually decrease with time for N SW . In addition, the regression with magnetosonic waves inside the plasmapause shows high coefficients around prenoon sector with preceding IMF B S and V SW . Key Points: We present the dependence of the magnetosonic wave amplitudes both outside and inside the plasmapause on the solar wind and AE index Southward IMF B z is the most influential parameter that affects the dayside wave amplitudes both outside and inside the plasmapause Solar wind number density contributes to enhancing the duskside waves outside the plasmapause